2009
DOI: 10.1140/epjb/e2009-00234-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of a Schelling segregation model

Abstract: The collective behavior in a variant of Schelling's segregation model is characterized with methods borrowed from statistical physics, in a context where their relevance was not conspicuous. A measure of segregation based on cluster geometry is defined and several quantities analogous to those used to describe physical lattice models at equilibrium are introduced. This physical approach allows to distinguish quantitatively several regimes and to characterize the transitions between them, leading to the buildin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
145
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(152 citation statements)
references
References 20 publications
5
145
0
2
Order By: Relevance
“…Each time point the lattice has a particular state defined by Equation (6), that produces a r t , which is the set of the homogeneity satisfactions for all the residential members of the lattice. These configurations can be treated as 'microstates' which change according the dynamics of the Schelling model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each time point the lattice has a particular state defined by Equation (6), that produces a r t , which is the set of the homogeneity satisfactions for all the residential members of the lattice. These configurations can be treated as 'microstates' which change according the dynamics of the Schelling model.…”
Section: Discussionmentioning
confidence: 99%
“…The work of [6] develops a method based upon the cluster geometry to measure the label segregation. Approaches to finding a spatial measure which captures obscure cases is an ongoing area of research and can be relied upon for specified classes of patterns [7] produces a physically inspired model for the gradient of the cluster formations so that the arrangements over the iterations resemble that in other physical phenomena but these states are still assess qualitatively by inspection as noted in [8].…”
Section: Introductionmentioning
confidence: 99%
“…Segregated regions may then appear as agents swap to neighbourhoods whose racial make-up is more to their liking. Subsequently, numerous authors ( [23,6,18,8,7]) have observed the structural similarity between this model and variants of the Ising model considered in statistical mechanics for the analysis of phase-transitions.…”
Section: Introductionmentioning
confidence: 93%
“…However, these approaches are limited to specific utility functions. More recently, physicists have tried to use a statistical physics approach to understand the segregation transition (12)(13)(14). The idea seems promising because statistical physics has successfully bridged the micro-macro gap for physical systems governed by collective dynamics.…”
mentioning
confidence: 99%